Frequency of Thyroid Neoplastic Lesions in Thyroidectomy Specimens - Amin Fahim, Aneela Qureshi, Sana Zulficiar, Sumreen Kashif, Hina Khan (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: To find out the histopathological pattern of neoplastic thyroid diseases in surgical thyroidectomy specimen and correlate them with age and gender. Study design: Descriptive study. Place & Duration: Department of Pathology Isra University Hyderabad Campus, from July 2011 to June 2013. Material & Methods: From 358 thyroidectomy specimens, 94 cases of any sex & age were selected for study having neoplastic thyroid lesions. Demographic data including clinical history, age and gender was collected by using printed proforma. Results: Among 94 cases. 66 were benign tumors with mean age 30.9±8.7 years, and the most common histopathological type was follicular adenoma (51 out of 66 cases) occurring with highest frequency in 21-30 years age. Number of malignant tumors was 28 with mean age 37.4±1.3 years, and papillary carcinoma was the most common histopathological type (19 out of 28 cases) occurring with increased incidence in 21-30 years age. Conclusions: The benign neoplastic lesions were found more common than malignant ones. Follicular adenoma and papillary carcinoma were the most common benign and malignant tumors respectively.